The Ripper affair - Saintcrow, Lilith (Saintcrow, Lilith. Bannon & Clare ;, 2014)
"A shattering accident places Archibald Clare, mentath in the service of Britannia, in the care of Emma Bannon, sorceress Prime. Clare needs a measure of calm to repair his faculties of Logic and Reason. Without them, he is not his best. At all. Unfortunately, calm and rest will not be found. There is a killer hiding in the sorcerous steam-hells of Londinium, murdering poor women of a certain reputation. A handful of frails murdered on cold autumn nights would make no difference ... but the killings echo in the highest circles, and threaten to bring the Empire down in smoking ruins. Once more Emma Bannon is pressed into service; once more Archibald Clare is determined to aid her. The secrets between these two old friends may give an ambitious sorcerer the means to bring down the Crown. And there is still no way to reliably find a hansom when one needs it most"--Page 4 of cover.